Verfahren zur Prädiktion des Rollwiderstands bei variablen Betriebsparametern auf Basis standardisierter Rollwiderstandsmessungen - Greiner, Matthias (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2019)
As a contribution to environmental protection, the EU tyre label was introduced. However, the best label value does not necessarily imply the lowest rolling resistance under real operating conditions. This research work aims to develop a model to predict the rolling losses of car tyres based on standardized rolling resistance measurements. Using this model, the rolling resistance at variable operating parameters will be predicted.